2001
DOI: 10.1096/fj.01-0646fje
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces translocation of glucose transporter GLUT4 to plasma membrane caveolae in adipocytes

Abstract: Insulin-stimulated glucose uptake in muscle and adipose tissue is the result of translocation of insulin-regulated glucose transporters (GLUT4) from intracellular vesicles to the plasma membrane. Here we report that GLUT4 in the plasma membrane of 3T3-L1 adipocytes were located predominantly in caveolae invaginations: by immunogold electron microscopy of plasma membranes, 88% of GLUT4 were localized to caveolae structures and this distribution within the plasma membrane was not affected by insulin. By immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 29 publications
4
69
0
5
Order By: Relevance
“…As a result, insulin triggering of glucose uptake is modulated upstream by retardation of insulin-dependent stimulation of 2-deoxy[ 3 H] glucose uptake, conceivably through impairment of insulin-stimulated translocation of phosphorylated Akt to caveolae and prevention of glucose transporter recruitment. This interpretation is consistent with previous studies reporting that disruption of caveolae domains in the plasma membrane impaired insulinstimulated glucose uptake in rat adipocytes and 3T3L1 adipocytes (Gustavsson et al, 1999;Parpal et al, 2001;Karlsson et al, 2002;Muller et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As a result, insulin triggering of glucose uptake is modulated upstream by retardation of insulin-dependent stimulation of 2-deoxy[ 3 H] glucose uptake, conceivably through impairment of insulin-stimulated translocation of phosphorylated Akt to caveolae and prevention of glucose transporter recruitment. This interpretation is consistent with previous studies reporting that disruption of caveolae domains in the plasma membrane impaired insulinstimulated glucose uptake in rat adipocytes and 3T3L1 adipocytes (Gustavsson et al, 1999;Parpal et al, 2001;Karlsson et al, 2002;Muller et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Carvalho et al, (2000) reported the impaired phosphorylation and insulin-stimulated translocation to the plasma membrane of Akt in adipocytes from type 2 diabetic subjects. Recent studies in rat adipocytes demonstrated that cholesterol depletion, which disrupts cholesterol-rich caveolae domain in the plasma membrane, impaired insulin-stimulated Akt activation and glucose uptake Parpal et al, 2001;Karlsson et al, 2002;Muller et al, 2002). Thus, it is interesting that the impairment of actin remodeling by the insulin resistance condition in H9c2 cardiomyoblasts is closely related to the retardation in Akt translocation to caveolae and a decrease in the amount of phospholylated Akt in caveolae for insulin-stimulated glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three caveolin isoforms, Cav-1 affects the function of many biologically important receptors and emzyme proteins (Couet et al, 1997;Lee et al, 2001;Schlegel et al, 2001;Liou et al, 2001;Jung et al, 2003;Cha et al, 2004;Jung et al, 2005). In addition, several transporter proteins are also anchored with and regulated by Cav-1 (McDonald et al, 1997;Bossuyt et al, 2002;Karlsson et al, 2002;Cai et al, 2004). In contrast to the extensive researches on Cav-1 or Cav-3, the study on the role of Cav-2 has been rather scant.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In addition, Cav-3 plays a role in the regulation of energy metabolism of muscle cells as it is required for the cell membrane targeting of phosphofructokinase, an enzyme that catalyzes a rate-limiting reaction in glycolysis. 13,14 In vitro studies have shown that Cav-3 plays a critical role in myoblast cell differentiation and survival and in myotube formation. 15 The relevance of Cav-3 in muscle physiology was further confirmed by the findings that mutations in the CAV3 gene result in distinct neuromuscular and cardiac disorders, such as limb girdle muscular dystrophy (LGMD) 1-C, idiopathic persistent elevation of serum creatine kinase (hyperCKemia), inherited rippling muscle disease (RMD), distal myopathy and familial hypertrophic cardiomyopathy (HCM).…”
mentioning
confidence: 99%